A Case Report of Improved Palmoplantar Pustulosis following Periodontal Treatment and Possible Association with Diminished Systemic Subclinical Inflammation - Akiko Yamashita; Tomomi Sano; Misaki Iwashita; Fusanori Nishimura (Hindawi Limited, 2021)
Palmoplantar pustulosis (PPP) is a recurrent pustular dermatosis located on the palms and soles. Focal infection may exacerbate the symptoms of PPP, but the etiology is not fully clear. A 56-year-old woman with PPP was diagnosed with severe chronic periodontitis. Initial treatment for periodontitis combined with topical application of antibiotics and surgical treatment was performed. In this case, attention was paid to the relevance of systemic inflammation caused by periodontitis with the clinical symptoms of PPP. With periodontal treatment, the symptoms of PPP and periodontitis, high-sensitivity C-reactive protein (hs-CRP) level, and periodontal inflamed surface area (PISA) improved. This case highlights the importance of comprehensive dental examinations, including those for oral infections, such as periodontitis and other unrecognized sources of infection, and dental treatment in the overall management of PPP.